Creative Power Refected In Paulo Coelho's Eleven Minutes Novel (2003): An Individual Psychological Approach - Pratamy, Rissa Nur (2016)
RISSA NUR PRATAMY. A320120015. CREATIVE POWER REFLECTED IN PAULO COELHO'S ELEVEN MINUTES NOVEL (2003): AN INDIVIDUAL PSYCHOLOGICAL APPROACH. RESEARCH PAPER. SCHOOL OF TEACHER TRAINING AND EDUCATION, MUHAMMADIYAH UNIVERSITY OF SURAKARTA, JANUARY 27, 2016. The major problem of this study is creative power. Someone who suddenly gets a creative power, she must experience a big change in her life. The objective of this study is to analyze this novel based on the Individual Psychological Approach. The researcher employs qualitative method. The writer uses two data sources: primary and secondary. The primary data sources of the study in Eleven Minutes novel by Paulo Coelho. Secondary data are the supporting data taken from literary books, criticism, and some articles related to the novel. The secondary data of the study are taken from any information related to the novel. The method of data collection is the researcher will employ the descriptive qualitative research. Based on the analysis, the researcher gets some conclutions. The study shows that the problem faced by the major character is her creative power. It is proven by her dream that becomes the better life. She is a prostitute woman. She wants to be successful person. Maria uses her creativity to manage her strategy. She should make every effort to cope with the problem of life.